UiTM lecturer shares government initiatives during Covid-19 - UiTM, Faculty of Business and Management (UiTM, 2021)
Dr J. S. Keshminder, Economics lecturer from the Faculty of Business and Management, (FBM), Universiti Teknologi MARA ( UiTM), Malaysia shared his thoughts on the challenges of Covid-19 and the government initiatives in facing them at various Malaysian TV programs(RTM and BERNAMA).